Analysis of the Emotions and Emotional Skills of University Students in Processing Distance Formative Feedback - Hausman, Matthieu; Leduc, Laurent; Malay, Laura; Delvaux, Sophie; Detroz, Pascal (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2023)
The aim of this study is to better understand the emotions that emerge in university students when processing feedback, how they affect the process, and the influence of emotional competencies and motivational beliefs. To this end, a questionnaire was developed to measure students’ emotional competencies, intensity of emotions associated with processing distance formative feedback, several components of motivational beliefs, and perceived usefulness of targeted feedback. This paper presents the results obtained from 52 students. The analyses show that the students’ emotional competencies are well developed, and that they experience a wide range of emotions when processing feedback. It was not possible to identify any significant links between the variables measured and the perceived usefulness of feedback. However, some are linked to the emotions experienced by students and their intensity, such as the score obtained and, to a lesser extent, certain motivational beliefs.